Levels of Lymphocytes, Neutrophils, Leukocytes and Outcome of Covid-19 Patients - Siahaan, Maniur Arianto; Purba, Sri Dearmaita; Amila, Amila (Alta Dharma Publisher, 2022)
Introduction: Coronavirus Disease 2019 can cause systemic infections that significantly affect the immune response and hemostatic conditions. A biomarker is needed to predict patients in the severity of the disease or severe complications or when doing triage upon admission to the hospital, providing early intervention, to reduce mortality. Changes in levels of lymphocytes, neutrophils. and leukocytes can predict the risk of worsening Covid-19 patients. Objective: to determine the effect of lymphocytes, neutrophils, and leukocytes on the outcome of Covid-19 patients. Method: This study uses an observational analytic design with a retrospective approach. The population of this research is medical records of Covid-19 confirmed positive by real-time Polymerase chain reaction (rt-PCR) from the Laboratory of H. Adam Malik General Hospital Medan for the period January-December 2021. Sampling using purposive sampling as many as 175 medical records. The test used to determine the relationship of lymphocytes, neutrophils, and leukocytes to the outcome of Covid-19 patients is the Spearman correlation test. Result: The results showed that there was a weak and positive relationship between lymphocytes (p = 0.006; r = 0.208) and the outcome of Covid-19 patients, there was a moderate and positive relationship between neutrophils (p = 0.000; r = 0.276) and the outcome of Covid-19 patients. moderate and positive relationship between leukocytes (p = 0.000; r = 0.350) and the outcome of Covid 19 patients. Recommendation: It is recommended to conduct a study in a large group by comparing the severity of the disease and the length of stay. Keywords: Covid-19, lymphocytes, neutrophils, leukocytes, outcome